PERANCANGAN SISTEM INFORMASI AKUNTANSI GUNA MENINGKATAN EFISIENSI DAN EFEKTIVITAS OPERASIONAL PERUSAHAAN - Arazy, Dito Rozaqi; Ismawanto, Totok; Yusrina, Yasmin Zulfati; Kusumawati, Ratna Dewi (Jurnal Riset Terapan Akuntansi, 2024)
To remain competitive in the industry, shipping companies must have an accounting information system that can be accessed quickly for their customers. The aim of this research is to find out how PT. Agung Sukowati Expedisi implements an accounting information system for the income, expenditure and general ledger cycles. This descriptive qualitative research uses case studies. Data was collected through direct observation, interviews and documentation. Data analysis uses matching, explanation and time series analysis. The research results will help partners assess how effective and efficient the company's accounting information system is. The product intended as an invention or innovation is an accounting information system that includes income and expenditure cycles as well as general ledgers and reports. The aim is to increase business productivity. This study will add to previous research on Accounting Information Systems. PT. Agung Sukowati Expedition provides goods delivery services. In order to compete with existing competitor companies, these companies must develop new services. The integration of an Accounting Information System in an organization will increase productivity and operational efficiency. In addition, with the existence of an Accounting Information System, organizations can create policies that are based on the actual problems faced by the organization, which are more targeted. Keywords: Accounting Information Systems, Expenditure Cycle, Reporting Cycle, Revenue Cycle